2015
DOI: 10.1186/s12888-015-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporary loss of moral behavior in a patient undergoing chemotherapy with cisplatin - breaking bad

Abstract: BackgroundBehavioral disturbances following chemotherapy with cisplatin are rare. Here, we report a patient with temporary loss of moral behavior in the setting of cisplatin-based chemotherapy for treatment of tonsillar cancer.Case presentationA 66-year-old Caucasian male with no psychiatric or violent history was started on chemotherapy with cisplatin for treatment of tonsillar cancer. During the following weeks, the patient developed profound personality changes involving volatile emotions and impulsive aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several reports have shown that cisplatin resistance appears mainly through faults in the apoptosis pathway as well as alteration in cisplatin aggregation in cells. It was reported that DNA injury caused by cisplatin stimulates phosphorylation of Bcl‐2‐related agonist of cell death by ERK and PI3K/AKT signalling pathways . Phosphorylation of Bcl‐2‐related agonist of cell death is indispensable to the viability of cisplatin‐resistance cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that cisplatin resistance appears mainly through faults in the apoptosis pathway as well as alteration in cisplatin aggregation in cells. It was reported that DNA injury caused by cisplatin stimulates phosphorylation of Bcl‐2‐related agonist of cell death by ERK and PI3K/AKT signalling pathways . Phosphorylation of Bcl‐2‐related agonist of cell death is indispensable to the viability of cisplatin‐resistance cells .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that DNA injury caused by cisplatin stimulates phosphorylation of Bcl-2-related agonist of cell death by ERK and PI3K/AKT signalling pathways. 26,27 Phosphorylation of Bcl-2-related agonist of cell death is indispensable to the viability of cisplatin-resistance cells. 28 Suppression of either pathway may enhance cisplatin sensitivity of a number of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was not until the patient's behaviour improved that cisplatin was suspected as being responsible for the symptoms. 8 The outcome of this case was positive, with the patient seeing a full return to his normal function. However, it seems that the patient's aggressive behaviour was the main reason cisplatin treatment was stopped.…”
Section: Cisplatin-induced Change In Moral Conscience and Behaviourmentioning
confidence: 79%
“…7 However, a recently reported case by Barlinn et al suggested that cisplatin may in fact be able to cause CNS impairment in rare cases, and may have been responsible for major neurological and behavioural changes in a man undergoing cisplatin treatment for tonsillar cancer. 8…”
Section: Introductionmentioning
confidence: 99%
“…After readjustment of antipsychotic therapy, symptoms subsided within 15 days. Table 2 [17,[81][82][83][84][85][86][87][88][89] summarizes chemotherapeutic agents associated with similar presentations.…”
Section: Chemotherapy-induced Mania: Should We Use Mood Stabilizers?mentioning
confidence: 99%